X-Ray Diffraction and SEM Investigation of Solidification/ Stabilization of Nickel and Chromium Using Fly ash - Ranjana A. Patil; Sangesh P. Zodape (E-Journal of Chemistry, 2011)
The main thrust of the paper is mechanism of immobilization of nickel(Ni) and chromium(Cr) metal sludge by solidification/stabilization using lime fly ash and sand (LFAS). The mineralogy of fly ash used for the study has been determined on the basis of x- ray diffraction analysis (XRD). Attempts have been made to investigate the consequences of interaction of heavy metal ion with constituents of lime fly ash sand composite on the basis of XRD studies and scanning electron microscopy (SEM, except chromium).